TRAINING FUTURE ORGANIZATION PRACTICAL PSYCHOLOGIST IN THE EDUCATIONAL PROCESS - Прудка, Л. М. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2013)
The paper theoretically grounded and presents an analysis of the forms and methods of the educational process for the effective training of future clinical psychologists in higher education institutions in order to create their productive knowledge, skills and integrative skills